Distributed MPP Tracking of PV through Buck Converter Using Fuzzy - Chandani Sharma; Anamika Jain (Institute of Advanced Engineering and Science, 2015)
Photovoltaics (PV) are the most abundant, perennial, environment friendly and distributed source of energy all over the globe. In this paper, the method to increase PV extraction efficiency for 60W panel with improved DMPP (Distributed Maximum Power Point) even on changing temperature and irradiance have been mapped and discussed. In order to achieve this, the components and subsystems have been analyzed and validated. The validated models are used to maximize the power output using two different models of DC-DC Converters in MATLAB/SIMULINK environment. Closed loop Buck converter using state space nonlinear differential equations and direct component model are compared to reveal best results at Standard Test Conditions (STC). MPPT model developed can be used for obtaining maximum power output from PV even in partial presence of sun using Fuzzy Logic Controller. The Controller designed tracks highest power output for the buck converter. The model developed, using tested membership functions in FLC, can serve a platform for various real time applications using PV.